Answer :

Join CA and BD.

Since arc DC subtends ∠DAC at the center and ∠CAB at point B in the remaining part of the circle, we have:

∠DAC = 2∠CBD ……………(1)

(Reason: In a circle, angle subtended by an arc at the center is twice the angle subtended by it at any other point in the remaining part of the circle.)

Similarly, arc BC subtends ∠CAB at the center and ∠CDB at point D in the remaining part of the circle, we have:

∠CAB = 2∠CDB ……………(2)

(Reason: In a circle, angle subtended by an arc at the center is twice the angle subtended by it at any other point in the remaining part of the circle.)

From equation (1) and (2), we have:

∠DAC + ∠CAB = 2∠CDB + 2∠CBD

⇒ ∠BAD = 2(∠CDB + ∠CBD)

⇒ 2(∠CDB + ∠CBD) = 1/2 (∠BAD)

Rate this question :

In the given figuRS Aggarwal & V Aggarwal - Mathematics

In Fig. 16.121, iRD Sharma - Mathematics

If *ABC* is RD Sharma - Mathematics

The chord of a ciRD Sharma - Mathematics